2020
DOI: 10.3390/pathogens9040304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Antimicrobial Susceptibility of C. jejuni Isolates from Italian Wild Bird Populations

Abstract: Poultry is considered a major reservoir of human campylobacteriosis. It also been reported that not only poultry, but also wild birds, are capable of carrying C. jejuni, thus demonstrating to be a risk of spreading the bacteria in the environment. To gain insight into the population structure and investigate the antimicrobial resistance genotypes and phenotypes, we analyzed a collection of 135 C. jejuni from 15 species of wild birds in Italy. MLST revealed the presence of 41 sequence types (STs) and 13 clonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
3
12
0
1
Order By: Relevance
“…This technique has been used in assessing Campylobacter strain overlap among different species of wild birds, poultry, and humans ( Colles et al, 2008 ; French et al, 2009 ; Hughes et al, 2009 ; Du et al, 2019 ; Wei et al, 2019 ; Jurinoviæ et al, 2020 ). Since the application of MLST is restricted to the sequence type characterization, whole-genome or core-genome MLST techniques are preferred for the accurate differentiation of related strains ( Marotta et al, 2020 ). Currently, technological advancements have enabled the use of a more advanced WGS technique, which reveals an organism’s entire DNA make-up ( Franz et al, 2016 ).…”
Section: Identification and Characterization Of Campylobactermentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been used in assessing Campylobacter strain overlap among different species of wild birds, poultry, and humans ( Colles et al, 2008 ; French et al, 2009 ; Hughes et al, 2009 ; Du et al, 2019 ; Wei et al, 2019 ; Jurinoviæ et al, 2020 ). Since the application of MLST is restricted to the sequence type characterization, whole-genome or core-genome MLST techniques are preferred for the accurate differentiation of related strains ( Marotta et al, 2020 ). Currently, technological advancements have enabled the use of a more advanced WGS technique, which reveals an organism’s entire DNA make-up ( Franz et al, 2016 ).…”
Section: Identification and Characterization Of Campylobactermentioning
confidence: 99%
“…Similarly, the study from Lithuania reported 87.1% resistance to ciprofloxacin ( Aksomaitiene et al, 2019 ). Another study from Italy reported resistance to tetracycline (12.5%), nalidixic acid (10%), ciprofloxacin (10%), streptomycin (6.7%), and erythromycin (4.2%) ( Marotta et al, 2020 ). To sum up, the antibiotic resistance pattern of Campylobacter in wild birds seems under-investigated, and thus, further studies are warranted.…”
Section: Drug Resistance Statusmentioning
confidence: 99%
“…Data about the potential role of wild avifauna as a fecal source of bacteria and parasites for humans and other mammals are not numerous, and in particular those concerning Italy are very scanty [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed the possibility of wildlife or environmental sources to act as reservoirs of Campylobacter infection ( Sheppard et al., 2009a ; Griekspoor et al., 2013 ; Cody et al., 2015 ; Atterby et al., 2018 ; Marotta et al., 2019 ; Marotta et al., 2020 ). In particular, these researchers focused on agricultural settings, especially on wild birds ( Sheppard et al., 2009a ; Griekspoor et al., 2013 ; Cody et al., 2015 ; Atterby et al., 2018 ; Marotta et al., 2019 ) small mammals ( Sippy et al., 2012 ) and insects ( Hald et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%